(untitled) (Journal of Hama University, 2024)
This study examines the impact of Corona pandemic on the profitability of Islamic banks listed at Damascus Securities Exchange using two proxies for profitability, Returns on Assets (ROA) and Returns on Equity (ROE), with a dummy variable that controls for Corona pandemic. To conduct this study, we collect financial data on three Islamic banks from the Syrian Commission of Financial Markets and Securities (SCFMS) for the period 2016 to 2022. Authors applied multiple linear panel regression to analyze data and test hypotheses. Results illustrated that operational efficiency and fees and commission ratio significantly affect ROA while only operational efficiency affects ROE. However, Corona pandemic had no impact on profitability indicators. This study recommends Islamic banks to improve their operational efficiency and search for other income sources to improve their profitability indicators. This study encourages the Central Bank of Syria to revise rules and regulations related to Islamic financing to ease its use in accordance with the reconstruction needs of the country and to motivate the investment and economic activities. Financial analysts should give a special attention to Islamic banks’ operational efficiency, particularly items related to fees and commissions, when estimating their future profits.